1952
DOI: 10.1149/1.2779711
|View full text |Cite
|
Sign up to set email alerts
|

A Hydride Bath for the Electrodeposition of Aluminum

Abstract: A process was developed for the deposition of aluminum from an ethereal solution of aluminum chloride and a metal hydride. The best deposits were obtained from an ethyl ether solution that was 2 to 3.M in aluminum chloride and 0.5 to 1.0M in lithium hydride. The deposits were quite ductile, and deposition rates of 0.025 to 0.05 mm per hour were possible. Deposits 0.5 to 0.75 mm thick were produced with hardnesses of from 37 to 97 Vickers.An investigation of the effect of various inorganic addition agents on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 8 publications
(10 reference statements)
1
54
0
1
Order By: Relevance
“…6,7,22 A previous spectroscopic study on 1.7 mol dm ¹3 diglyme solution of AlCl 3 (cf. 1.4 mol dm ¹3 in this study) showed that the system consists of molecular species (AlCl 3 ·diglyme) and ionic ones of four-Cl-coordinated AlCl 4 ¹ and six-O/Cl-coordinated [AlCl 2 (diglyme) 2 ] + . 27 Therefore the sufficient conductivity should result from the sizable amount of the ionic Al species.…”
Section: ¹2supporting
confidence: 49%
See 1 more Smart Citation
“…6,7,22 A previous spectroscopic study on 1.7 mol dm ¹3 diglyme solution of AlCl 3 (cf. 1.4 mol dm ¹3 in this study) showed that the system consists of molecular species (AlCl 3 ·diglyme) and ionic ones of four-Cl-coordinated AlCl 4 ¹ and six-O/Cl-coordinated [AlCl 2 (diglyme) 2 ] + . 27 Therefore the sufficient conductivity should result from the sizable amount of the ionic Al species.…”
Section: ¹2supporting
confidence: 49%
“…Besides, the media range from high temperature molten salts, 3 organic solvents e.g. ethers, 4,5 aromatic hydrocarbons, [6][7][8][9] and dimethylsulfone (DMSO 2 ), [10][11][12][13][14][15] and ionic liquids (ILs). [16][17][18][19][20][21] Although the high temperature baths have mainly been used for industrial Al electrorefining, medium-low and/or room temperature (RT) baths are anticipated as promising Al electroplating and/or Al battery electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition which is commercially most important 577 » 673 > is that of Al by the NBS process 684,685) . The plating bath is a mixed electrolyte solution of LiAlH 4 (0.2-0.4 M) and AlCl 3 (3 M) in anhydrous DEE.…”
Section: Selected Examplesmentioning
confidence: 99%
“…[17][18][19][20][21] At present, only two commercial processes on the basis of organic solvents are available for electroplating of Al: SIGAL 10,22 and REAl 23,24 processes. Although high quality Al coating can be obtained by these processes, because of their relatively narrow electrochemical window, low conductivity, low solubility of aluminium salts, higher volatility and flammability, the applications of these organic solvent systems in electrodeposition of Al are limited.…”
Section: Introductionmentioning
confidence: 99%